MODERN RADIOTHERAPY FOR PEDIATRIC RHABDOMYOSARCOMA - Popović-Vuković, Marija; Nidžović, Borko; Nikitović, Marina (Medicinski podmladak, 2020)
Rhabdomyosarcoma is the most common soft tissue sarcoma among children and represents half of all soft tissue sarcomas. Tumor is derived from primitive mesenchymal stem cells which develop into striated muscle and common sites of occurrence are the head and neck region, genitourinary tract and extremities. Treatment is multimodal and includes surgery, radiotherapy and chemotherapy. Application of combined treatment led to significant improvement in treatment outcome. Due to long-term survival, great importance is given to the expected treatment complications. Therapy for pediatric rhabdomyosarcoma requires a delicate balance between the need to intensify therapy for certain group of patients and the desire to reduce potentially toxic therapy and risk for secondary malignancies for patients with good prognosis. Radiotherapy plays an important role in local control of disease and is performed in nearly all patients. Since it is applied to organs and tissues that are in growth and development phase, radiotherapy in childhood has its own specificity and represents greater challenge in relation to the treatment of adult patients. The use of modern radiotherapy techniques ensures excellent local control of disease with better sparing of normal surrounding tissues which reduces radiotherapy toxicity and preserves quality of life of treated children.